Hepatic Autophagy Deficiency Compromises Farnesoid X Receptor Functionality and Causes Cholestatic Injury. Issue 5 (8th March 2019) - Khambu, Bilon; Li, Tiangang; Yan, Shengmin; Yu, Changshun; Chen, Xiaoyun; Goheen, Michael; Li, Yong; Lin, Jingmei; Cummings, Oscar W.; Lee, Youngmin A.; Friedman, Scott; Dong, Zheng; et al.
Abstract : Autophagy is important for hepatic homeostasis, nutrient regeneration, and organelle quality control. We investigated the mechanisms by which liver injury occurred in the absence of autophagy function. We found that mice deficient in autophagy because of the lack of autophagy‐related gene 7 or autophagy‐related gene 5, key autophagy‐related genes, manifested intracellular cholestasis with increased levels of serum bile acids, a higher ratio of tauromuricholic acid/taurocholic acid in the bile, increased hepatic bile acid load, abnormal bile canaliculi, and altered expression of hepatic transporters. In determining the underlying mechanism, we found that autophagy sustained and promoted the basal and up‐regulated expression of farnesoid X receptor ( Fxr ) in the fed and starved conditions, respectively. Consequently, expression of Fxr and its downstream genes, particularly bile salt export pump, and the binding of FXR to the promoter regions of these genes, were suppressed in autophagy‐deficient livers. In addition, codeletion of nuclear factor erythroid 2‐related factor 2 ( Nrf2 ) in autophagy deficiency status reversed the FXR suppression. Furthermore, the cholestatic injury of autophagy‐deficient livers was reversed by enhancement of FXR activity or expression, or by Nrf2 deletion. Conclusion: Together with earlier reports that FXR can suppress autophagy, our findings indicate that autophagy and FXR form a regulatory loop and deficiency of autophagy causes abnormal FXR functionality, leading to the development of intracellular cholestasis and liver injury.